Safety Culture Among Car Drivers and Motorcycle Riders in Norway and Greece: Examining the Influence of Nationality, Region, and Transport Mode - Nævestad, Tor-Olav; Laiou, Alexandra; Yannis, George (Frontiers in Sustainable Cities, 2020)
The aims of the study are to (1) compare the road safety behaviors among car drivers and motorcyclists in five different regions in Norway and Greece, (2) examine the factors influencing the road safety behaviors in these groups, and (3) examine the relationship between road safety behaviors and accident involvement. The study is based on survey answers from car drivers and motorcycle riders in two Greek and three Norwegian regions (N = 1,212). Road safety culture (RSC) is defined as shared patterns of behavior and shared expectations to other road users. The results indicate shared national RSC among Norwegian riders and drivers in the three Norwegian regions. The results from the Greek sample indicate the importance of the regional level for RSC and a unique RSC on the studied Greek island. The data do not indicate that transport mode is important for road safety behaviors or RSC. Our analyses indicate that RSC is important as it is closely related to road safety behaviors, which in turn is related to accident involvement. This suggests that accidents may be reduced by influencing the RSC. To contribute to such efforts, we discuss how and where RSC is created and how it influences road safety behavior, based on our results.